Diversity, floral phenology, and socio-economic importance of melliferous plants in Eastern Ethiopia - AMARE FASSIL; TSEGAW HABTAMU; MUHDIN TAHIR; TEMESGEN TEREFE (Nusantara Bioscience, 2022)
Abstract. Fassil A, Habtamu T, Tahir M, Terefe T. 2022. Diversity, floral phenology, and socio-economic importance of melliferous plants in Eastern Ethiopia. Nusantara Bioscience 14: 172-181. Beekeeping is a supply of extra money and financial gain for many thousands of farmer beekeepers in Ethiopia and plays a big role in preserving natural resources. Honeybees and flowering plants have co-evolved in their special symbiotic relationship. Bee plant types and their flowering duration differ from one place to another due to variations in topography, climate, and other cultural and farming practices. This study investigated and documented the diversity and floral phenology of honeybee plants in Doba, Gemechis, and Mi’eso Districts, Oromia National Regional State, Eastern Ethiopia, from January 2019 to July 2021. Ethnobotanical data were collected to reveal the diversity of melliferous plants, practices, and communities’ attitudes about honey production and melliferous plant conservation. A total of 422 respondents participated through semi-structured interviews, focus group discussions, and field walks for socio-economic data collection. Descriptive statistics such as frequencies, ranking, and scores were used and presented with tables and figures to analyze ethnobotanical data. A total of 120 melliferous plant species were distributed under 108 genera and 55 families, of which 70 plants were found in the Gemechis District, followed by Doba and Mi’eso Districts with 47 and 42 plants each, respectively. Sorenson’s Similarity Index values showed the wide-ranging melliferous plant species distribution patterns in the three districts with 50.4 (between Doba and Mi’eso), 37.5 (between Doba and Gemechis), and 15.3 (between Gemechis and Mi’eso) species overlaps. Fabaceae and Asteraceae contribute a significant number of species, with 12 (10 %) and 9 (7.5 %) melliferous plants, respectively. Local communities have a good awareness of the seasonal availability of melliferous plants, indicating adequate supply (June to early December) and critical shortage (November to early May) of melliferous plant resources favoring strong and weak colony strength, respectively. Lack of nutrition, improper management practices, honey bee predators, and lack of beekeeping knowledge and equipment were the most important constraints deleteriously influencing the honey quality and amount in the study area. The shortage of pollen and nectar flow during the dearth periods (January to March) needs interventions like hive migration and bee floral plantations. Hence, there is an urgent need for intervention through awareness creation, campaign-based melliferous plant plantations, and technology transfers.